Contos de fadas e a construção da imagem simbólica coletiva frente à inclusão escolar - Tanaka, Luciene Martins (2007)
The present work has as objective to discuss the influence of the construction of the collective image on the deficiency and difference, that in elapsing of the history, it was constituted in a social memory, that it came interfering in the formation of faiths and values, as well as resulting in certain resistance attitudes to the students' inclusion with deficiency in the schools of regular teaching. This way, we left of the questioning on the ' how' and 'why', so many values and faiths with historical bases, persist on that new millennium, resulting many times in attitudes, behaviors prejudicies to the children's inclusion with deficiency, or considered different from the pattern had as 'normal', in social or school ambit, above all in the fundamental regular teaching of 1st to 4th series. Now, in a time in what so much is talked about integration, social inclusion, inclusive school, will reason be that found several attitudes of the teachers front to the students' inclusion with any deficiency type? It is not our intention to do any species of those professionals' judgement, but yes of we understand the reason of certain behaviors they stay in the new century. We have yes the intention of proposing a reflection on the form as our social memory is constituted and in this way crystallized along the time, making possible the professionals of the education, a critical vision and conscious of the posture type that we will adopt in ours to do and to live pedagogic, prioritizing the citizens' formation with different faiths and values, of the to today perpetuated. By means of an education compromised and conscious, we can facilitate a social transformation, adopting resistance attitudes to the exclusion, to the discrimination, with an interactive relationship, seeking a democratized education and for everybody, executing its inclusive function of guaranteeing the access, the permanence, but above all the right of learning of each human being. For that, he/she becomes necessary that there are an weakening of the authoritarian power, moralist and standard of living in the texts of the Infantile Literature (especially of the stories of fairies), giving to the reader a larger autonomy of thinking and of forming a conscious collective symbolic image, close to the Real and, above all, more humanitarian.